Constructicography : Constructicon Development Across Languages. - Lyngfelt, Benjamin. (Constructional Approaches to Language Series, 2018)
This is the first major publication devoted to constructicon development and it should be particularly relevant for those interested in construction grammar, frame semantics, lexicography, the relation between grammar and lexicon, or linguistically informed language technology.